Making Something from Anything: Entrepreneurial Education as a Catalyst for Entrepreneurial Bricolage in Gen-Z - Tanesia, Cindy Yoel; Utami, Christina Whidya; Chandra, Michelle Gabriel (Universitas Brawijaya, Indonesia, 2025)
Entrepreneurial activity is an important driver of economic development in a country. However, Indonesia still has a low number of entrepreneurs compared to the total population due to limited resources and institutional barriers. Thus, it is crucial to understand how entrepreneurship education may foster creative and adaptive behavior, such as entrepreneurial bricolage, especially in Generation Z, who are predicted to be the economic drivers of Indonesia in the future. This study aims to examine the relationship between entrepreneurial education and entrepreneurial bricolage, considering the mediating effects of entrepreneurial self-efficacy and entrepreneurial capacity. A quantitative approach was employed by distributing surveys to 400 Gen-Z respondents who had taken an entrepreneurship course in universities, and the data were analyzed using PLS-SEM. The results of the study show that entrepreneurial education has a strong impact on entrepreneurial self-efficacy and entrepreneurial capacity. In addition, both variables were also found to mediate the relationship between entrepreneurial education and entrepreneurial bricolage partially. These findings indicate that the transformation from entrepreneurship education toward bricolage behavior happens through psychological readiness and strengthening entrepreneurial capacity. The novelty of this study lies in positioning entrepreneurial bricolage as the outcome of entrepreneurial education, achieved by integrating Social Cognitive Theory and Effectuation Theory in the context of Generation Z in Indonesia. Theoretically, this study enhances the understanding of the mechanism underlying the formation of entrepreneurial behavior, and practically guides the development of an entrepreneurship education curriculum.